Treatment of women’s social problems of emancipation, spinsterhood and divorce from an Islamic perspective - Haroun, Mohamed Jibril Fadel; Mohamed, Mohamed Ali Ahmed; Khalifa, Yasser Hassan Ahmed (Arab Journal for Sciences and Research Publishing, 2017)
This research aims to identify, from an Islamic perspective, the social problems that women suffer from today such as liberation, becoming spinster and divorce as well as how these problems could be tackled, the researcher adopted the descriptive and analytic methodology to conduct the study, the reached many findings, the most significant of which are: It is important that all customs which have adverse impact on women should be combated and Islam holds a positive and comprehensive view towards women and There is no difference between men and women in regard to their duties and competencies.